Risk factors for and short-term prognosis of intrauterine infection in preterm infants - Xuemei Zhao; Yue Song; Liqun Lu (Journal of International Medical Research)
Objective To identify the risk factors for and short-term prognosis of intrauterine infection (IUI) in preterm infants. Methods We retrospectively collected clinical data regarding preterm infants (28 +0 –36 +6 weeks of gestational age) with IUI from the neonatal intensive care unit of our hospital between June 2017 and June 2022. The pathologic characteristics of the infants were classified using the Redline criteria, and the resulting groups were compared with respect to their clinical characteristics, indicators of infection, complications, and mortality rates. Results Three hundred thirty (78.1%) of the 422 enrolled neonates showed signs of histologic IUI; 51.8% showed histologic chorioamnionitis alone, and 48.2% showed both histologic chorioamnionitis and funisitis. The independent risk factors identified for IUI were maternal prenatal invasive manipulation, premature rupture of membranes (>18 hours before labor), and prenatal C-reactive protein concentration. The infants with IUI showed higher incidences of respiratory distress syndrome, bronchopulmonary dysplasia, retinopathy of prematurity, and prolonged mechanical ventilation. Low gestational age and low birth weight of preterm infants were significantly associated with a higher incidence of histologic IUI, more severe inflammation, and a higher incidence of complications. Conclusions Histologic IUI is associated with high complication and mortality rates in preterm infants, as is an increasing severity of inflammation.